DETERMINATION OF PG12S SURFACTANT PHASE BEHAVIOUR IN THE MIXTURE OF OIL - SURFACTANT - COSURFACTANT - WATER - Tjuwati Makmur; Nuraini Nuraini (Testing Center for Oil and Gas LEMIGAS, 2008)
Surfactant is surface active agent chemical, while isopropyl alcohol (IPA) and also isobutyl alcohol (IBA) are known as cosurfactant and include types of alcohols used in enhanced oil recovery (surfactant flooding) method. Factors of surfactant, cosurfactant, and NaCl concentrations play important role in determination of phase behavior. Based on the results of phase behavior tests that the mixture of oil – PG12 surfactant – cosurfactant (IPA & IBA) – WIP water showed macroemulsion phase for all analyzed samples at different experimental conditions. PG12 surfactant is unable to be used for enhanced oil recovery by chemical injection, because it is very difficult to flow in porous media and to displace oil, because the occurrence of plugging which is caused by opaque and milky macroemulsion.